Sosoialisasi Pencegahan Bullying pada Murid SDN 18,26,22,41,38 Sungai Limau, Untuk Meningkatkan Partisipasi dan Antusiasme Siswa dalam Pencegahan Bullying - Ena Noveria; Muhammad Arif Pribadi; Akmal Muhammad Ali Nasution; Zaskya Adya Mecca; David Rivan; Olvi Sagita; Muzakki Fankas (CV. ITTC INDONESIA, 2026)
As an integral part of the community service contributions of Universitas Negeri Padang, students play a crucial role in applying various fields of knowledge gained during their studies for the advancement of society across different sectors. In line with this principle, Community Service Program (CSP) students from Universitas Negeri Padang actively participated through the implementation of a socialization program conducted in the Sungai Limau region during the January june 2026 period. The program carries the theme